WONG TUWO AS A MODEL OF CONFLICT RESOLUTION IN THE TARIQA QADIRIYAH WA NAQSYABANDIYAH - Masduki Masduki; Imron Rosidi; Toni Hartono (Khazanah: Jurnal Studi Islam dan Humaniora, 2022)
This article analyzes a conflict resolution model practiced among the followers of the Tariqa Qadiriyah wa Naqsyabandiyah. This research uses a philosophical and ethnographic method to analyze the social life of the followers of Tariqa Qadiriyah wa Naqsyabandiyah in Riau, Indonesia. Through these methods, this article finds that the Tariqa followers have established a conflict resolution philosophy called the Wong Tuwo. This philosophy appears from the concept of an individual as a peacebuilder that has to live and has character harmoniously, friendly, and ethically among human beings beyond ethnicity, culture, and religion. The "Wong Tuwo" provides sophisticated way the Tariqa followers solve problems and prevent potential conflict in the community. One of the essential things of this model is that peaceful figures, as reflected in Wong Tuwo, are believed to be role models for building quiet life, social interaction, and communication among human beings.